Limitations on the Freedom of Movement of Foreigners and Asylum Seekers in Croatian Law and Practice - Staničić, Frane (Law, Identity and Values, 2024)
In reality, numerous measures can be issued that limit the freedom of movement of foreigners, including third country nationals and asylum seekers. Detaining foreigners and asylum seekers is a form of deprivation of freedom of movement and can be compared to incarceration as they can be either arrested and detained for a short period of time or detained at the Centre for foreigners. The second form of detention is more important as it can last for a relatively long period. There are numerous reasons for which a foreigner can be detained at the Centre; moreover, the detainment can be prolonged repeatedly. This is why a scrutinous control of decisions to detain a foreigner must be established and every decision of detention must be controlled by an administrative court ex officio. This represents a quasi-administrative dispute instigated ex officio to ensure the conformity of such decisions with the law. This study analyzes the legal regulation of detention of foreigners. as well as the practice of the courts to show whether the Ministry of Interior acts in accordance with the law.